Adaptive AHP: a review of marketing applications with extensions - Davies, Mark (European journal of marketing, 2001)
A review of marketing applications of the analytic hierarchy process (AHP) shows that major concerns involve the accuracy of knowledge elicitation and choice of a suitable knowledge base. Decision support is suggested with a series of decision rules based on different variations of AHP for both structuring and evaluation, presented in the user interface. Models that solved historical information needs can also be adapted for current marketing conditions by incorporating AHP within a marketing knowledge-based decision support system (KB-DSS). Current decision rules might be chosen on the basis of past behaviour that has proved successful, sharing similar marketing conditions and characteristics, captured within a suitable knowledge base. Decision rules are then chosen on the basis of their relevance to the current problem, based on historical AHP case data that are continuously revised. This proposal reduces data collection and processing time.